Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Bank Syari’ah - Muhammad Aldino; Rahmat Hidaya; Maya Panorama (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Good corporate governance, or GCG, is essential to achieve the primary goal of all financial institutions, including Islamic banks, which is to improve financial performance. How the financial performance of banks is affected when Good Corporate Governance (GCG) is implemented in Islam is the main concern of this study. Islamic banks must balance adherence to moral standards with financial efficiency to uphold Shariah principles in practice. Therefore, it is imperative to understand the extent to which GCG involvement can significantly enhance the financial success of Islamic banks. This study uses quantitative methodology that includes multiple regression analysis and descriptive techniques. Secondary data can be found in the annual reports of Islamic banks for a certain period of time registered with the Financial Services Authority (OJK). Several GCG indicators have been analyzed, including the sharia supervisory board, audit committee, board of commissioners structure, and information transparency. When evaluating financial performance measures, Return on Equity (ROE) and Return on Assets (ROA) ratios are used. An investigation is conducted to confirm the causal relationship between these parameters.